2019
DOI: 10.1016/j.sleep.2018.10.039
|View full text |Cite
|
Sign up to set email alerts
|

The role of parental circadian preference in the onset of sleep difficulties in early childhood

Abstract: Background: Chronotype is a construct contributing to individual differences in sleep-wake timing. Previous studies with children have found that evening-types exhibit greater sleep difficulties. Infant sleep quality can be modulated by several factors, such as parental characteristics. We examined the association between parental circadian preference and sleep in early childhood. Methods: This study was based on a longitudinal birth cohort, with several measurement points. We used information regarding parent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…Sleep problems have been found to be greater in evening types compared to morning types, both in toddlers (Simpkin et al., ) and preschool children (Jafar et al., ), and a change towards the circadian preference for evening hours appears to occur already in toddlers (Randler, Faßl, & Kalb, ). In addition, recent findings from our group suggest that maternal circadian preference is related to several sleep difficulties of infants in early childhood, and especially to increased risk of slower sleep–wake rhythm development (Morales‐Muñoz et al., ).…”
Section: Discussionmentioning
confidence: 88%
“…Sleep problems have been found to be greater in evening types compared to morning types, both in toddlers (Simpkin et al., ) and preschool children (Jafar et al., ), and a change towards the circadian preference for evening hours appears to occur already in toddlers (Randler, Faßl, & Kalb, ). In addition, recent findings from our group suggest that maternal circadian preference is related to several sleep difficulties of infants in early childhood, and especially to increased risk of slower sleep–wake rhythm development (Morales‐Muñoz et al., ).…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, this experimental design, does not identify if a specific period of gestation or postnatal development is more crucial for the development of metabolic syndrome. Maternal, but not paternal, circadian preference was found to be associated with infants' circadian rhythm development in early childhood (Morales-Munoz et al 2019). Recent studies also suggest that chronodisruption during the neonatal period, when synchronization of the infant's circadian rhythms occur, might have long and short-term health consequences, potentially causing chronic stress-associated disorders (Astiz & Oster 2018, McKenna & Reiss 2018.…”
Section: Effects Of Maternal Circadian Chronodisruption On Fetal and mentioning
confidence: 99%
“…In addition to studies with objective parameters, future studies should further examine the interaction between eveningness and morningness within the family, and whether maternal eveningness also impacts child sleep quality at preschool age, similar to the impact in infancy [ 19 ]. Conversely, paternal eveningness does not seem to impact infant sleep problems [ 19 ]. However, in this study, child eveningness also affected paternal sleep.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Understandably, the chronotypes of family members seem to interact: previous studies have shown that the maternal chronotype is highly correlated with that of the child and a male partner [ 18 ]. Maternal eveningness has been shown to increase infant sleeping problems [ 19 ], and eveningness of other family members seems to increase feelings of somnolence and even the caffeine and alcohol consumption of a morning-type adult member of the family [ 20 ].…”
Section: Introductionmentioning
confidence: 99%